2014
DOI: 10.1021/ed4009057
|View full text |Cite
|
Sign up to set email alerts
|

Use of Doceri Software for iPad in Online Delivery of Chemistry Content

Abstract: Doceri software for iPad is useful for both synchronous online and asynchronous online delivery of chemistry course content. Using the Doceri wireless connection between the iPad and a personal computer that is running Adobe Connect, online synchronous instruction can be accomplished in which drawings can be completed by hand on the iPad. For asynchronous delivery, lectures can be easily recorded by Doceri on the iPad. As with synchronous lectures, the content on display can be easily annotated over, making it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…As shown in Figure 1, Doceri and ScreenFlow software tools were utilized for elaborating asynchronous video lectures. Particularly, Doceri software was a very useful alternative tool, which can deliver science classes to multiple distance campuses with synchronous and asynchronous online instruction [32]. The instructors encouraged the students watching the video lectures before the class based on the class schedule.…”
Section: Flipped-cclassroom Instructinal Designmentioning
confidence: 99%
“…As shown in Figure 1, Doceri and ScreenFlow software tools were utilized for elaborating asynchronous video lectures. Particularly, Doceri software was a very useful alternative tool, which can deliver science classes to multiple distance campuses with synchronous and asynchronous online instruction [32]. The instructors encouraged the students watching the video lectures before the class based on the class schedule.…”
Section: Flipped-cclassroom Instructinal Designmentioning
confidence: 99%
“…Particularly, tools such as PowerPoint slides or Doceri were used to grab the video-lectures, which have proved to be effective delivering the multimedia of science contents (Silverberg Lee et al 2014;Fitzgerald and Li 2015). This feature was well rated by the students, since nearly 80 % of them considered that the Fig.…”
Section: Perceptions' Evaluationmentioning
confidence: 99%
“…In addition to presentation programs, many instructors of chemistry use blackboards (or whiteboards) actively, because the use of blackboards makes it easier to control the pace of lectures and allows students to follow the details more closely. It has been shown that tablet PCs with interactive whiteboard apps could be used in teaching chemistry. , Even without sophisticated apps, tablet PCs can be very useful in online chemistry lectures, providing the opportunity to write or draw directly on PowerPoint slides with stylus pens. The author used an Android tablet PC whose screen was mirrored onto a Windows 10 PC…”
Section: Introductionmentioning
confidence: 99%